Distribution of p63, cytokeratins 5/6 and cytokeratin 14 in 51 normal and 400 neoplastic human tissue samples using TARP-4 multi-tumor tissue microarray - Reis Filho, Jorge S. (2003)
p63, cytokeratin (CK) 5/6 and CK 14 have been employed in diagnostic pathology as markers of basal, squamous and myoepithelial differentiation in several types of human neoplasms; however, there is scant data on the concurrent expression of these markers in large series of human neoplasms. We analyzed the distribution of these three immunohistochemical markers in 51 normal human tissue samples, 350 carcinomas, 25 malignant melanomas (MMs), and 25 glioblastomas using three serial sections of tissue array research program (TARP)-4 multi-tumor tissue microarray. Also, we performed double immunostainings to characterize the differential distribution of p63/CK 5/6 and p63/CK 14 in normal breast, salivary gland and skin. p63, CK 5/6 and CK 14 were expressed in basal cells of the prostate and respiratory epithelia and in breast and bronchial myoepithelial cells. p63 was also expressed in cytotrophoblast cells of human placenta and in scattered cells of lymph node germinal center. CK 5/6 and CK 14 also stained the cytoplasm of basal cells of esophageal stratified squamous epithelium and transitional epithelial cells of the bladder. No mesenchymal, neural, endothelial, smooth muscle or adipose cells were stained by any of the markers. p63, CK 5/6, and CK 14 were respectively expressed in 92.6%, 75.0%, and 52.9% of the squamous cell carcinomas of the lung, 10.2%, 20.0%, and 7.4% of the ductal carcinomas of the breast, 12.9%, 34.4%, and 11.8% of the serous and 25.0%, 0%, and 0% of the endometrioid carcinomas of the ovary. Lung, prostate and colonic adenocarcinomas, as well as MMs and glioblastomas were only rarely decorated by one of the markers. Only matched samples of 16 squamous cell carcinomas and two ductal carcinomas of the breast co-expressed these three markers. In double immunostainings, p63-CK 5/6, as well as p63-CK 14 were co-expressed by basal/ myoepithelial cells of the salivary glands and basal cells of the epidermis. Our results demonstrate that p63, CK 5/ 6 and CK 14 may be used together in immunohistochemical panels to characterize squamous differentiation in poorly differentiated carcinomas or carcinomas of unknown origin.